(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Change in dietary pattern and a better economic situation in India has resulted in non communicable diseases like heart ailments, diabetes, obesity etc. Irrespective of any age group, children, adults, elderly population are at the risk of these health problems in India. Objective: To study the gender wise comparison of the health problems among Hotel Management students in India. Methodology: Subjects (n=94) were selected through random sampling comprising of both male and female in age group 18 to 25 years. A questionnaire was used to collect the data regarding personal history and habits. Blood Pressure was monitored using sphygmomanometer. Hemoglobin was measured using automated Heamoglobinometer. BMI (kg/m2) and Body Fat (BF%) was measured using a commercially available digital weight scale incorporating a bioelectric impedance analyzer (HBF-352, Omron Health care Co., Kyoto, Japan) based on bioelectric impedance analysis. All statistical calculations were done using STATA IC 13 software. Results: Body Fat% was higher among females than males. Among both male and female students, dietary habits were mostly non-vegetarian. Male students with non vegetarian dietary habits (88.7%) were significantly higher than females (p<0.05). The prevalence of overweight and obese cases according to BMI in male students was 19.1% and 20.6% respectively, whereas in case of female students 26.9% were overweight and 23.1% were obese. Male students had significantly higher mean values of systolic (p<0.001) and diastolic (p<0.001) blood pressure. Significantly higher anemia cases in moderate category were observed in female students (p<0.05).Conclusion: The present study showed higher prevalence of obesity and hypertension among students in the age group 18-25 years. Interventions are required to combat the obesity related health impairments.